Review: Poetter, Thomas S. Curriculum Fragments: A Currere Journey Through Life Processes. - Joseph Wiederhold (Journal of the Assembly for Expanded Perspectives on Learning, 2025)
Poetter’s book Curriculum Fragments—and the stories shared within— have changed the way I think about education. Redefined it. Recentered it on what matters most—the human experience, the life processes at the center of Poetter’s book: losing, knowing, forgiving, relating, hoping, growing, loving. Each of Poetter’s fragments—reflective narratives written following the Currere methodology (Pinar)—caused me to reevaluate my practice.